Relationships of endocrine cells to each other and to other cell types in the human gastric fundus and corpus - Fakhry, Josiane (Cell Tissue Res, 2018)
Gastric endocrine cell hormones contribute to control of the stomach and to signalling to the brain. In other gut regions, enteroendocrine cells (EEC) exhibit extensive patterns of colocalisation of hormones. In the current study, we characterised EEC in the human gastric fundus and corpus. We utilised immunohistochemistry to investigate EEC with antibodies to ghrelin, 5-HT, somatostatin, PYY, GLP-1, calbindin, gastrin and pancreastatin, the latter as a marker of enterochromaffin like cells (ECL). EEC were mainly located in regions of the gastric glands populated by parietal cells. Gastrin cells were absent and PYY cells were very rare. Except for about 25% of 5-HT cells being a subpopulation of ECL cells marked by pancreastatin, colocalisation of hormones in gastric EEC was infrequent. Ghrelin cells were distributed throughout the fundus and corpus; most were basally located in the glands, often very close to parietal cells, and were closed cells, that is, not in contact with the lumen. A small proportion had long processes located close to the base of the mucosal epithelium. The 5-HT cells were of at least 3 types; small round closed cells, cells with multiple, often very long, processes, and a sub-group of ECL cells. Processes were in contact with their surrounding cells, including parietal cells. Mast cells had very weak or no 5-HT immunoreactivity. Somatostatin cells were closed type with long processes. In conclusion, four major chemically-defined EEC types occurred in the human oxyntic mucosa. Within each group were cells with distinct morphologies and relationships to other mucosal cells.